(untitled) - Bob Leasure; Bob Leasure (Boston, MA., 2003)
Designed for a first course in database technologies, this book completes the trilogy for the Web Warrior Guide To books (the other two titles cover Web Design Technologies and Web Programming). Using the Java platform, students are taught how to create data-driven Web sites while implementing the latest technologies such as relational databases, MySQL, XML and JSP. Theory is presented early on, but the emphasis in this book is placed on the detailed hands-on learning skills required to work with these technologies
Keywords: Web sites - Design